2016
DOI: 10.1002/tox.22323
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to butyl paraben impairs testicular structure and sperm quality on male rats

Abstract: Parabens are hormonally active chemicals widely used as preservatives in foods and are frequently detected in human fluids and tissues. Therefore, the objective of this study was to determine the effects of maternal butyl paraben (BP) exposure on male sexual development. Pregnant Wistar rats received corn oil (control group), or BP at doses of 10, 100, or 200 mg/kg, subcutaneously, from gestational day 12 until postnatal day 21. Our results demonstrated that developmental BP exposure significantly increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 86 publications
(103 reference statements)
3
18
1
Order By: Relevance
“…According to a U.S. National Health and Nutrition Survey, urinary BP was detected at a concentration of 0.2–1240 μg/L in 47% of the population . Maternal exposure to BP causes problems with the development of reproductive organs in male offspring in rats . In addition, prenatal exposure to BP causes impaired neurodevelopment .…”
Section: Discussionmentioning
confidence: 99%
“…According to a U.S. National Health and Nutrition Survey, urinary BP was detected at a concentration of 0.2–1240 μg/L in 47% of the population . Maternal exposure to BP causes problems with the development of reproductive organs in male offspring in rats . In addition, prenatal exposure to BP causes impaired neurodevelopment .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ERS1 knockout mice show infertility at adulthood (Shibayama et al, 2001) and fluid accumulation in the testis, an abnormal concentration of sperm and compromised sperm maturation in the caput of epididymis (Hess, 2014). Furthermore, a decreased ERS1 expression is also related to increased sperm abnormalities, decreased sperm motility (Couse & Korach, 1999;Guerra et al, 2016) and reduced sperm counts (Couse & Korach, 1999). In this study, the control group exhibited similar moderate cytoplasmic staining for ERS1 in the round and elongated spermatids and in Leydig cells, as previously described (Guerra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a decreased ERS1 expression is also related to increased sperm abnormalities, decreased sperm motility (Couse & Korach, ; Guerra et al, ) and reduced sperm counts (Couse & Korach, ). In this study, the control group exhibited similar moderate cytoplasmic staining for ERS1 in the round and elongated spermatids and in Leydig cells, as previously described (Guerra et al, ). Moreover, the Leydig cells showed a strong nuclear staining for ERS1, which is in accordance with a previous study (Pelletier, Labrie, & Labrie, ).…”
Section: Discussionmentioning
confidence: 99%
“…Butylparaben (butyl 4-hydroxybenzoate, BP) from the paraben family has widely been used as antimicrobial/ antifungal preservative in cosmetic products, deodorants, toiletries, face creams, pharmaceuticals, toys, food, and beverages for more than 50 years (1,2). Parabens are endocrine disruptors which impair natural metabolism of hormones by mimicking, interfering, and/or blocking them (3)(4)(5)(6).…”
mentioning
confidence: 99%